Historical Developments of China's Xinjiang Province or Western Region - Zreik, Mohamad (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
In this study, the author examines the history of Xinjiang, which has since become a province of China and a vital component of the mainland's culture. This research is entirely based on secondary sources using historical research methods. In addition to the analytical descriptive technique, the functional approach was allotted. According to the findings, ethnic and religious diversity abounds in Xinjiang. Even though Xinjiang has been the site of several conflicts and invasions, the Silk Road has made it a more vital commercial route for the region's ethnic groups and neighboring countries. Xinjiang's residents followed a variety of faiths, including Zoroastrianism, Buddhism, and Islam.